Teachers’ Strategies in Overcoming Students’ Speaking Difficulties in English: A Case Study of Eighth Grade Students at MTsN 1 Mataram - Agustina, Aulin; Lestari, Yuni Budi; Herayana, Desi (LITPAM, 2026)
This research is based on the understanding that difficulty speaking English as a foreign language is a complex phenomenon involving various factors. This study aims to identify the speaking difficulties faced by eighth-grade students at MTsN 1 Mataram and to analyze the strategies used by English teachers to overcome those difficulties. This research employed a qualitative descriptive approach with a case study design. The participants consisted of two English teachers and six eighth-grade students selected through purposive sampling. The data were collected through classroom observations and semi-structured interviews. The findings revealed that students experienced several speaking difficulties, namely limited vocabulary, poor grammar knowledge, and pronunciation challenges. Among these difficulties, limited vocabulary was identified as the most dominant factor affecting students’ speaking performance. To overcome these problems, teachers implemented various strategies and role-play was found to be the most effective in overcoming students’ speaking difficulties. Role-play provided students with opportunities to practice vocabulary, sentence construction, and pronunciation in meaningful contexts while increasing their confidence and participation. Other strategies, such as small group discussions, storytelling, and games, also supported students’ speaking development. Overall, the study indicates that role-play is the most effective strategy in addressing students’ speaking difficulties. This study reinforces previous findings that limited vocabulary is a major obstacle in learning to speak English in EFL contexts at the junior secondary level. This finding implies that teaching interventions need to prioritize vocabulary enrichment as a foundation before expecting students to be able to produce fluent and accurate speech.